2006
DOI: 10.1007/s00383-006-1788-3
|View full text |Cite
|
Sign up to set email alerts
|

Congenital diaphragmatic hernia: onset of respiratory distress and size of the defect

Abstract: The purpose of this study was to evaluate the outcome in neonates with congenital diaphragmatic hernia (CDH) either presenting within the first 24 h of life or diagnosed prenatally. The study was particularly focused on the time of onset of respiratory distress and on the use of the Gore-Tex (GT) patch for diaphragmatic reconstruction. Records of 104 neonates with CDH were retrospectively reviewed. The data were analyzed by ANOVA, Kruskal-Wallis test or chi (2) test as appropriate. The result showed that the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In one review of 104 patients diagnosed either antenatally or within the first 24 hours of life, 18 infants were found to have additional defects. The most common defect was congenital heart disease, followed by renal anomalies, spina bifida, Pierre-Robin syndrome, Fryns syndrome, esophageal atresia, omphalocele, and choledochal cyst [3]. In another case series of late-presenting CDH, 40% were diagnosed with mid-gut malrotation, 7% with multicystic kidney disease, and 7% with a spinal cord deformity [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one review of 104 patients diagnosed either antenatally or within the first 24 hours of life, 18 infants were found to have additional defects. The most common defect was congenital heart disease, followed by renal anomalies, spina bifida, Pierre-Robin syndrome, Fryns syndrome, esophageal atresia, omphalocele, and choledochal cyst [3]. In another case series of late-presenting CDH, 40% were diagnosed with mid-gut malrotation, 7% with multicystic kidney disease, and 7% with a spinal cord deformity [4].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 80% to 95% of cases are diagnosed by antenatal ultrasound with many of the remaining cases diagnosed within the first 24 hours of life [2, 3]. Rarely, patients develop herniation through a diaphragmatic defect beyond the immediate newborn period.…”
Section: Introductionmentioning
confidence: 99%
“…The management protocol has been described previously 10 and was identical for all patients. Extracorporeal membrane oxygenation (ECMO) was not used in any of the patients.…”
Section: Methodsmentioning
confidence: 99%
“…Despite advances in antenatal diagnosis and postnatal management, mortality rate remains stable around 40-50% [1][2][3][4]. It has been shown that overall survival rate is mainly determined by the rate of antenatal termination, the incidence of CDH associated anomalies, degree of pulmonary hypoplasia and pulmonary hypertension in the neonatal period [1,2,[5][6][7]. Reports of improved survival of CDH should be interpreted with caution, as variations in outcomes are more likely to be explained by case selection bias [2].…”
Section: Introductionmentioning
confidence: 99%